Rights and freedoms and guarantees of their implementation in the Yemeni constitutional system (With a constitutional reading of the draft Federal Constitution of Yemen) - Noman, Loei Tharesh (Journal of Economic, Administrative and Legal Sciences, 2022)
This research deals with the role of the Yemeni constitutional legislator in dedicating rights and freedoms, both in the constitutional amendment of 2001 AD as well as in the draft Federal Constitution of Yemen for the year 2015, and what is the extent of success in that? Therefore, we tried to highlight the most important guarantees to activate those rights, and we made the most important recommendations to address this.